Reading development in European Portuguese: relationships between oral reading fluency, vocabulary and reading comprehension - Fernandes, S.; Querido, L.; Verhaeghe, A.; Marques, C.; Araújo, L. (Reading and Writing, 2017)
This study investigated direct and indirect effects between oral reading fluency, vocabulary and reading comprehension across reading development in European Portuguese. Participants were 329 children attending basic education, from grade 1 to grade 6. The results of path analyses showed that text reading fluency is much more dependent on the foundational skills of word recognition than reading comprehension, and the later, in turn, depends crucially on the specific constituent skill of text reading fluency. Text reading fluency has a significant influence on vocabulary from the beginning, but vocabulary contributed to reading comprehension only in more advanced grades. These results, obtained with an orthography of intermediate depth, are in line with the Simple View of Reading (SVR). However, they also highlight the importance of textual cues—besides the pivotal role of decoding—from the beginning of learning to read, which must be taken into account in the SVR.